3.8k views
0 votes
How is the graph of y = negative RootIndex 3 StartRoot x minus 4 EndRoot transformed to produce the graph of y = negative RootIndex 3 StartRoot 2 x minus 4 EndRoot?

2 Answers

3 votes

Answer:

c on ed

Explanation:

i j did it

User Eric Tobias
by
5.6k points
2 votes

Answer:

Multiply by ∛2 and translate the graph to left by 4 units.

Explanation:

The initial function given is:

y = -∛(x - 4)

The transformed function is:

y = -∛(2x - 4)

Consider the initial function.

y = -∛(x - 4)

(Represented by Black line in the graph)

Multiply the function by ∛2. The function becomes:

y = -∛(x - 4) × ∛2

y = -∛(2)(x-4)

y = -∛(2x-8)

(Represented by Red line in the graph represents this function)

Translate the graph 4 units to the left by adding 4 to the x component:

y = -∛(2x-8+4)

y= -∛(2x - 4)

(Represented by Blue line in the graph)

How is the graph of y = negative RootIndex 3 StartRoot x minus 4 EndRoot transformed-example-1
User KIDJourney
by
5.0k points